Small interfering RNA mediated Poly (ADP-ribose) Polymerase-1 inhibition upregulates the heat shock response in a murine fibroblast cell line - Zingarelli Basilia; Gefter Julia V; Sjodin Hanna; Aneja Rajesh K; Delude Russell L (BMC, 2011)
Abstract Poly (ADP-ribose) polymerase-1 (PARP-1) is a highly conserved multifunctional enzyme, and its catalytic activity is stimulated by DNA breaks. The activation of PARP-1 and subsequent depletion of nicotinamide adenine dinucleotide (NAD+) and adenosine triphosphate (ATP) contributes to significant cytotoxicity in inflammation of various etiologies. On the contrary, induction of heat shock response and production of heat shock protein 70 (HSP-70) is a cytoprotective defense mechanism in inflammation. Recent data suggests that PARP-1 modulates the expression of a number of cellular proteins at the transcriptional level. In this study, small interfering RNA (siRNA) mediated PARP-1 knockdown in murine wild-type fibroblasts augmented heat shock response as compared to untreated cells (as evaluated by quantitative analysis of HSP-70 mRNA and HSP-70 protein expression). These events were associated with increased DNA binding of the heat shock factor-1 (HSF-1), the major transcription factor of the heat shock response. Co-immunoprecipitation experiments in nuclear extracts of the wild type cells demonstrated that PARP-1directly interacted with HSF-1. These data demonstrate that, in wild type fibroblasts, PARP-1 plays a pivotal role in modulating the heat shock response both through direct interaction with HSF-1 and poly (ADP-ribosylation).